ARV1 p.Gln62Ter, a novel mutation linked to developmental and epileptic encephalopathy-38 - Mostafa Neissi; Ayoob Radhi Al-Zaalan; Misagh Mohammadi-Asl; Mojdeh Roghani; Javad Mohammadi-Asl; Kamele Jorfi (Journal of Rare Diseases)
Abstract Developmental and epileptic encephalopathy is a rare and severe form of inherited neurodegenerative disorder characterized by various forms of seizures. This condition typically manifests between 4 and 7 months. Recent investigations have established a correlation between mutations in the ARV1 gene and the development of developmental and epileptic encephalopathy-38. Here, we report a 4-year-old girl from a consanguineous Iranian family diagnosed with developmental and epileptic encephalopathy-38. The patient presented with seizures, microcephaly, and abnormal MRI findings. Despite conventional anti-seizure drugs, seizures persisted from infancy. Tragically, her elder sibling with identical symptoms succumbed to the condition at 11 months. In this case report, we performed whole exome sequencing in an individual diagnosed with developmental and epileptic encephalopathy-38 in an Iranian family, revealing a novel homozygous mutation in the ARV1 gene (c.184C > T [p.Gln62Ter] in exon 2, NM_022786.3). Parental carriers displayed no symptoms, underscoring the importance of whole exome sequencing for accurate diagnosis and informed family planning decisions. These findings contribute to the understanding of the genetic spectrum of developmental and epileptic encephalopathy-38. The use of whole exome sequencing revealed a rare and likely pathogenic ARV1 gene mutation, emphasizing the significance of this genetic screening method in unraveling the complexities of developmental and epileptic encephalopathies.